Analisis Postur Kerja Operator Menggunakan Metode Rapid Entire Body Assesment (REBA) di Stasiun Pengisian Tawas PDAM Tirta Meulaboh - Marlinda Marlinda; Yusi Hidjrawan; Endi Saputra; Risnadi Irawan (Universitas Teuku Umar, 2022)
This study aimed to analyze the operator's work posture using the Rapid Entire Body Assessment (REBA) method and to determine the level of risk of Musculoskeletal Disorders (MsDs) on the alum filling station operator at PDAM Tirta Meulaboh. Based on the observations made on the operator's activities while working, the operator fills the alum with a bent body position, uses a shovel and lifts it and is done repeatedly. This research is a quantitative descriptive study, with direct observation of the process of filling alum. Data collection is done by taking photos of the operator's activities while doing his job, then determining the angle of the operator's body using the Rapid Entire Body Assessment (REBA) method. The conclusions is that the operator's working posture with REBA method gets a score for element I with a score of 6, element II with a score of 8, and element III with a score of 7 and the level of risk through Action Level. REBA score element I final score (4-7) moderate risk category with required action, element II final score (8-10) high risk category with urgent action required, and element III final score (4-7) moderate risk category with required action.